2021
DOI: 10.1017/dmp.2021.30
|View full text |Cite
|
Sign up to set email alerts
|

Idea Generation Through Hackathon Event in Emergencies and Disasters, with Emphasis on Managing Flash Flood Disaster

Abstract: Objective: This study was intended to demonstrate the applicability of the hackathon in idea generation for managing emergencies and disasters with a particular focus on flash floods. Methods: A 4-day hackathon event was held, having 60 students, 9 mentors and 6 judges gathered to explore different ideas, and to solve problems of Iran flooding from mid-March to April, 2019. Of these, 10 teams with 6 students were accordingly formed to brainstorm and discuss the idea, while 9 mentors offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…We retrieved 127 publications from additional searches (ie, citation searching and the complementary open call), with a further 11 publications included in this review. In total, we included 42 studies in this review,7 8 18–57 with 39 studies (93%) focusing on developing social innovations 7 8 18–20 22–42 44–53 55–57. The PRISMA flowchart is presented in online supplemental figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We retrieved 127 publications from additional searches (ie, citation searching and the complementary open call), with a further 11 publications included in this review. In total, we included 42 studies in this review,7 8 18–57 with 39 studies (93%) focusing on developing social innovations 7 8 18–20 22–42 44–53 55–57. The PRISMA flowchart is presented in online supplemental figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 41 studies (98%) reported the number of designathon participants 7 8 18–53 55–57. The median number of individuals participating in designathons was 49 (IQR 34–90, range 6–434), and the median number of teams was 8 (IQR 5–14.5, range 2–40).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though hackathons have originated from the software development community (e.g., cybersecurity, game jams, opensource development, and operating systems) (Nolte et al, 2018), they are increasingly popular in other domains such as crowdsourcing innovation (Temiz, 2021;Wang et al, 2021). Further, as society faces progressively more global challenges, the help of citizens-and more broadly crowds-is also being used to find solutions to universal problems such as carbon emissions, household waste, and deforestation through collective idea generation (Monsef et al, 2021).…”
Section: Settingmentioning
confidence: 99%